2014
DOI: 10.1063/1.4866991
|View full text |Cite
|
Sign up to set email alerts
|

Initial stages of ITO/Si interface formation: In situ x-ray photoelectron spectroscopy measurements upon magnetron sputtering and atomistic modelling using density functional theory

Abstract: Initial stages of indium tin oxide (ITO) growth on a polished Si substrate upon magnetron sputtering were studied experimentally using in-situ x-ray photoelectron spectroscopy measurements. The presence of pure indium and tin, as well as Si bonded to oxygen at the ITO/Si interface were observed. The experimental observations were compared with several atomistic models of ITO/Si interfaces. A periodic model of the ITO/Si interface was constructed, giving detailed information about the local environment at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Peaks of In2 and Sn2 belong to incomplete oxides of Indium and Tin accordingly. The O1 peaks corresponding to the dative bond of Indium and Tin oxides, while, the O2 peak indicates the existence of oxygen vacancy [14][15][16]. After 650 seconds, approaching the ITO interface, O3, In3, Sn3 peaks are beginning to emerge on the XPS spectral of In3d 5/2 , Sn3d 5/2 and O1s with the increase of etching depth.…”
Section: Xps Depth Profile Of Intermediate Regionmentioning
confidence: 94%
See 2 more Smart Citations
“…Peaks of In2 and Sn2 belong to incomplete oxides of Indium and Tin accordingly. The O1 peaks corresponding to the dative bond of Indium and Tin oxides, while, the O2 peak indicates the existence of oxygen vacancy [14][15][16]. After 650 seconds, approaching the ITO interface, O3, In3, Sn3 peaks are beginning to emerge on the XPS spectral of In3d 5/2 , Sn3d 5/2 and O1s with the increase of etching depth.…”
Section: Xps Depth Profile Of Intermediate Regionmentioning
confidence: 94%
“…are fitting peaks of single-crystal ITO film [14][15][16]. Among them, peaks of In1 and Sn1 are characteristic peaks of In 2 O 3 and SnO compounds correspondingly.…”
Section: Xps Depth Profile Of Intermediate Regionmentioning
confidence: 98%
See 1 more Smart Citation
“…Molecular dynamics calculations on ITO/c‐Si structure revealed that oxygen from ITO was attracted to the Si phase, initiating formation of SiO x . Similarly, the first stage of metallic In and Sn formation was indicated via several metal‐O bonds being broken in the MD models .…”
Section: Introductionmentioning
confidence: 88%
“…In a previous paper we have studied the formation of ITO/c‐Si interface with a combination of density functional theory‐based molecular dynamics (DFT‐MD) and in situ XPS. Presence of photoelectron peak components related to pure indium and tin as well as Si bonded to oxygen at the ITO/Si interface were detected.…”
Section: Introductionmentioning
confidence: 99%